Promotion of Politeness in Indonesian Language on Social Media & Navigating the Use of AI in Literary Works : Penyuluhan Kesantunan Berbahasa Indonesia di Media Sosial & Menyiasati Penggunaan AI dalam Karya Sastra - Munira Hasjim; Lukman; Muhammad Darwis; Inriati Lewa; Kaharuddin; Rismayanti; Indarwati (Universitas Lancang Kuning, 2023)
This counseling aims to increase awareness of the importance of using polite and respectful language in online communication, as well as to preserve the authenticity and uniqueness of literary works in the digital era. The method used in this community service is through counseling and training for students of the Indonesian Literature Department, Faculty of Cultural Sciences, Mulawarman University in Samarinda, especially social media users and literary writers. Counseling is conducted through workshops, seminars, and online campaigns to introduce the principles of politeness in the Indonesian language and provide examples of appropriate usage on social media. Meanwhile, the exploration of AI usage in literary works is conducted through research and experiments to discover new ways of creating unique and original literary works by utilizing AI technology. The results of this community service are increased awareness and understanding among students of the importance of using polite language on social media, as well as the development of new techniques in creating literary works that utilize AI technology.